E-Tax system, Socialization, and Tax Awareness on MSME Compliance: The Moderating Role of Understanding Level - Zalwa Fiqrianti Andini; Andi Wawo; Della Fadhilatunisa (Journal of Applied Taxation and Policy, 2025)
This study examines the influence of the tax e-system, socialization, and tax awareness on MSME tax compliance, and examines whether the relationship is strengthened by the level of taxpayer understanding. This study is a quantitative study with a quantitative descriptive approach. The sampling method used is simple random sampling with a sloving formula based on the number of MSME taxpayers. The results show that the e-system, socialization, and awareness have a positive effect on MSME compliance. Analysis of moderating variables shows that the level of understanding strengthens the e- system and socialization on MSME compliance, but the level of understanding does not strengthen tax awareness among MSME taxpayers.